Finite-Time Consensus Control for MASs Under Hidden Markov Model Mechanism - Nie, Rong; Du, Wenli; Li, Zhongmei; He, Shuping (IEEE transactions on automatic control, 2024)
This study focuses on the finite-time consensus tracking problem for multi-agent systems (MASs) subject to random abrupt changes via distributed asynchronous sliding mode control (SMC). In particular, Markov jump model is exploited to describe the random abrupt changes in MASs parameters caused by external factors. Moreover, considering the nonsynchronization between the controller mode and the system mode caused by the delayed measurements between agents, a continuous-time hidden Markov model is constructed to simulate this situation, in which the introduced mode-independent detector can directly observe the unmeasured information. Besides, by designing a novel distributed asynchronous SMC law, some sufficient conditions are provided to ensure fast consensus within a finite-time interval. Different from the existing SMC mechanisms, the proposed mechanism involves common sliding mode surface (SMS), which plays an important role in preventing the system trajectories from escaping from the SMS during the mode jump. Finally, numerical simulation results illustrate the feasibility of proposed control method.